2016
DOI: 10.1186/s13071-016-1384-x
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to deltamethrin affects development of Plasmodium falciparum inside wild pyrethroid resistant Anopheles gambiae s.s. mosquitoes in Uganda

Abstract: BackgroundPyrethroid resistance in African vector mosquitoes is a threat to malaria control. Resistant mosquitoes can survive insecticide doses that would normally be lethal. We studied effects of such doses on Plasmodium falciparum development inside kdr-resistant Anopheles gambiae s.s. in Uganda.MethodsWe collected An. gambiae s.s. homozygous for kdr-L1014S mutation, fed them on blood samples from 42 P. falciparum-infected local patients, then exposed them either to nets treated with sub-lethal doses of delt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 28 publications
3
45
2
Order By: Relevance
“…We explicitly considered only the acute lethality of insecticide exposure in our model as the overall toll that insecticide resistance and sub-lethal doses of insecticide may impose on mosquitoes and parasites is only now being investigated [44]. As the incidence and severity of resistance increases in wild populations, understanding the biological effects of sub-lethal insecticide exposure will be increasingly important.…”
Section: Discussionmentioning
confidence: 99%
“…We explicitly considered only the acute lethality of insecticide exposure in our model as the overall toll that insecticide resistance and sub-lethal doses of insecticide may impose on mosquitoes and parasites is only now being investigated [44]. As the incidence and severity of resistance increases in wild populations, understanding the biological effects of sub-lethal insecticide exposure will be increasingly important.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, pyrethroid resistance has become the greatest obstacle in the control of mosquito-borne diseases. Moreover, studies have shown that fitness costs associated with insecticide resistance may influence vector-borne disease transmission either by directly reducing the mosquito life span and fecundity, altering mating behaviours or impairing parasite development inside vectors [59][60][61][62]. Regardless, the extent to which resistance to insecticides interferes with the impact of mosquito-borne diseases in Jintun town is still unknown.…”
Section: Plos Onementioning
confidence: 99%
“…In addition, field‐collected kdr homozygous mosquitoes that were experimentally infected with malaria and subsequently exposed to deltamethrin impregnated bed nets showed a lower prevalence and lower intensity of infection compared to infected mosquitoes exposed to untreated bed nets. The deployment of resistance mechanisms by the mosquito could potentially be toxic to the parasite (Kristan et al., ). On the other hand, kdr mutations have been correlated with increased sporozoite prevalence, both in laboratory setting (Alout et al., , ) and in the field (Kabula et al., ; Ndiath et al., ).…”
Section: Antimalarial Interventions and Their Evolutionary Consequencesmentioning
confidence: 99%